DIRECTIONS OF UKRAINE'S INTEGRATION INTO GLOBAL VALUE CHAINS (INNOVATIVE ECONOMY, 2025)
Mytsenko V.І. DIRECTIONS OF UKRAINE'S INTEGRATION INTO GLOBAL VALUE CHAINSPurpose. The aim of the article is to systematize the directions of Ukraine's integration into global value chains, taking into account the sectoral, regional, institutional, and digital dimensions, as well as to align these directions with the priorities of economic security and the transition from an export-raw material model to a high value-added model.Methodology of research. The methodological basis of the study comprises a systems, structural and logical analysis, institutional and comparative approaches, as well as the synthesis of scientific findings of domestic and foreign researchers in the field of global value chains. The systemic approach was used to analyse Ukraine’s participation in GLSVs at the macro, meso and micro levels, taking into account production, logistics, institutional and digital factors. Structural and logical analysis ensured the sequential identification of key sectors and areas for deepening Ukraine’s integration into the GVCs. The institutional approach was used to evaluate the impact of the regulatory environment, state policy and international support on the resilience of value chains in the face of military challenges. The comparative approach allowed us to compare models of Ukraine’s participation in GVCs in different periods and sectors. The synthesis of scientific sources contributed to the formation of comprehensive conclusions regarding the prospects for Ukraine’s integration into global value chains with high added value. Findings. The article demonstrates that global value chains have become the dominant form of organization of contemporary global economic relations, within which countries are positioned not so much as producers of finished goods but rather as performers of specific functions – from raw material supply to processing, logistics, services, quality control, and compliance with environmental standards. It is substantiated that digital transformation should be considered a horizontal infrastructure for Ukraine’s integration into GVCs and includes the implementation of ERP and logistics systems, electronic registries, customs and phytosanitary clearance services, as well as traceability and certification platforms. The key role of institutional factors is identified, in particular the harmonization of the regulatory framework with EU law, improvement of quality and safety standards, and the development of mechanisms for monitoring the risks of participation in GVCs. Originality. It has been substantiated that the integration of Ukraine into global value chains in the context of military and post-military transformations is a multi-level process that combines sectoral, regional, institutional and digital dimensions. Unlike sectoral approaches, this allows for a comprehensive evaluation of the quality of a country’s participation in GLVC from the perspective of economic resilience and security. The role of the agricultural sector has been further developed through the substantiation of the transition from a raw materials-based model to an integrated model involving deep processing and the development of agrologistics. The approach to determining the directions of Ukraine’s integration into the GVCs has been improved by taking into account the digital transformation of the horizontal infrastructure of the value chains, which increases the adaptability and competitiveness of national producers.Practical value. The results of the study can be used when forming state and regional economic policy, developing sectoral strategies and programmes to support enterprises, and promoting Ukraine's participation in global value chains.Key words: global value chains, integration, value added, digitalization, logistics, economic security, sustainable development.
Keywords: global value chains; integration; value added; digitalization; logistics; economic security; sustainable development